Propagandizing anti-vaccination: Analysis of Vaccines Revealed documentary series. Issue 8 (18th February 2020) - Bradshaw, Amanda S.; Treise, Debbie; Shelton, Summer S.; Cretul, Matthew; Raisa, Aantaki; Bajalia, Alexis; Peek, Daisha
Graphical abstract: Highlights: Centers for Disease Control allegedly hid research on vaccine risks. Doctors increased credibility, prompting identification with the message. Panelists appealed to religious and ethical reasons for individual vaccine choice. Convoluted jargon, statistics, and misleading claims were presented. Gut-wrenching testimonials and sensationalism discouraged vaccination. Abstract: Politically charged health propaganda films may have public health ramifications through decreased vaccination uptake, especially with expansive dissemination potential on social media. The nine-episode documentary series Vaccines Revealed, touted as foremost truth within the largest anti-vaccination closed Facebook group, advocates for non-medical childhood vaccination exemptions — a policy actively opposed by the American Academy of Pediatrics. This series is recommended specifically to parents who are on the fence about whether or not to vaccinate their children as well as new, first-time, and expectant mothers. Fourteen 'expert' panelists included: six M.D, 's who reportedly prefer natural approaches for everything from chiropractic to cardiology practice, a vaccine injury attorney, two professors, one psychiatrist, the founder of natural search engine Greenmedinfo.com, a nationally-recognized clinical research expert on the HPV vaccine, the president of the National Vaccine Information Center, and three parents of vaccine-injured children. Additionally, voiceover clips from an epidemiologist and former senior scientist at the CDC were played throughout the series as evidence of governmental conspiracy. Inclusion of these testimonies, particularly from white coat doctors, led to a perception of high source credibility. Qualitative analysis of this documentary series revealed five overarching themes: (perceived) solidified science, collusion and conspiracy, canary in the coal mine, fear appeals, and the morality and necessity of individual choice. As opposed to formulating a priori theoretical assumptions, grounded theory allowed an integrative theoretical explanation to emerge from the data. Researchers expanded cognitive dissonance, parasocial interaction, and social identification theories and described how viewers of Vaccines Revealed could come to align their views on vaccinations with those of the panelists featured in the videos.